The Effect of Lighting Duration on the Density and Growth of Spirulina sp. - Wulan Purnami, Baiq; Abidin, Zaenal; Alim, Sahrul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Microalgae Spirulina sp. is a blue-green autotrophic organism that has a cylindrical cell structure that forms twisted filament colonies resembling spirals, and is usually used as a natural feed in aquaculture. Development has been carried out for the production of Spirulina sp. which includes culture techniques in various production scales, but the culture of Spirulina sp. cannot rely solely on the natural environment. The study aims to evaluate the effect of lighting duration on the density and growth of Spirulina sp. The lighting duration tested was 24 hours and 12 hours using the LED light, which was replicated 8 times. The density, doubling time, growth, and spirulina biomass were analyzed statistically using the T-test. The study showed that lighting duration affected (p<0,05) spirulina's density, growth, and biomass at the 48th hour of the culture period. Spirulina reached the peak of the growth at the 48th hour. The 24th-hour lighting showed a higher density of 53,615 sin per ml than the 12-hour lighting of 38.175 sin/ml. The spirulina growth of 24-hour lighting of 0,012 sin per day was higher than 12-hour lighting of 0,004 sin per day. In biomass, the 24-hour lighting resulted in 0,249+0,02 g higher than 12-hour lighting 0,143+0,07 g. However, there is no difference (p>0,05) in doubling time between 24 and 12 hours of lighting. The study suggests using 24-hour instead of 12-hour lighting to improve performance and growth.